Tectono-magmatic events of the Qilian orogenic belt in northern Tibet: new insights from detrital zircon geochronology of river sands. Issue 8 (24th May 2021) - Zhang, Shuo; Jian, Xing; Pullen, Alex; Fu, Ling; Liang, Hanghai; Hong, Dongming; Zhang, Wei
ABSTRACT: The Precambrian–Palaeozoic evolution of the Qilian orogen is widely debated due to the complexity of the orogen's structure and the extent of Phanerozoic deformation. In order to identify the tectono-magmatic events of the Qilian orogenic belt, we conducted detrital zircon U-Pb geochronology on river sediments across the orogen. The results indicate that the detrital zircon ages mainly comprise five populations: 220–280 Ma, 400–520 Ma, 800–1000 Ma, 1200–2100 Ma, and 2200–2700 Ma. The sediments in the Central Qilian Block exhibit zircon age peaks at ~1.8 Ga and ~1.0 Ga, which support that the Central Qilian Block successively accreted to the Columbia and Rodinia supercontinents. The sediments in the Quanji Block exhibit zircon age peaks at ~1.8 Ga and ~2.5 Ga, revealing possible affinity of the Quanji Block to the North China Craton prior to the Neoproterozoic. The detrital zircon age population in 400–520 Ma of all the sediments recorded the continental aggregation process among the Quanji, Qaidam, and Central Qilian Blocks. The widespread 200–300 Ma zircon ages in Central Qilian, Quanji, and North Qaidam regions, reflect a tectono-magmatic event which was most likely associated with the low-angle Paleo-Tethys subduction at the southern margin of Qaidam Block. Our results underline that the overlooked Neoarchean to Paleoproterozoic and Permian to Triassic tectono-magmatic events of the Qilian orogenic belt deserves more attention in the future study. The detrital zircon age populations of different river sand samples indicate fairly high variability, highlighting that caution should be exercised while using modern river sand detrital zircon age signatures to track tectono-magmatic history of such complex orogens.